2001
DOI: 10.1080/01431160010028490
|View full text |Cite
|
Sign up to set email alerts
|

Global monitoring of interannual changes in vegetation activities using NDVI and its relationships to temperature and precipitation

Abstract: Interannual trends in annual and seasonal vegetation activities from 1982 to 1990 on a global scale were analysed using the Path® nder AVHRR Land NDVI data set corrected by utilising desert and high NDVI areas. Climate eVects on interannual variations in NDVI were also investigated using temperature and precipitation data compiled from stational observations. In the northern middlehigh latitudes, vegetation activities increased over broad regions because of a gradual rise in temperature. NDVI increases were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 10 publications
5
67
0
4
Order By: Relevance
“…5c). The data show that the NDVI is, statistically, more closely linked with surface temperature than precipitation, in agreement with previous findings (Ichii et al 2002;Kawabata et al 2001;Los et al 2001;Schultz and Halpert 1993). Schultz and Halpert (1993) found that the onset of precipitation generally appears to act as the stimulus for vegetation in regions where the magnitude of the annual temperature cycle is small, and vice versa.…”
Section: The Climate Factors Related To Ndvi (Amj)supporting
confidence: 90%
See 1 more Smart Citation
“…5c). The data show that the NDVI is, statistically, more closely linked with surface temperature than precipitation, in agreement with previous findings (Ichii et al 2002;Kawabata et al 2001;Los et al 2001;Schultz and Halpert 1993). Schultz and Halpert (1993) found that the onset of precipitation generally appears to act as the stimulus for vegetation in regions where the magnitude of the annual temperature cycle is small, and vice versa.…”
Section: The Climate Factors Related To Ndvi (Amj)supporting
confidence: 90%
“…Vegetation activity is strongly influenced by the local weather variables, so researchers have identified the local meteorological variables associated with the NDVI, such as air temperature, precipitation and evapotranspiration (Di et al 1994;Kawabata et al 2001;Nemani and Running 1989;Wang et al 2003). However, large-scale climate systems also play essential roles in how the NDVI changes in response to global change (Gong and Shi 2003).…”
mentioning
confidence: 99%
“…While other more recently developed indices for vegetation characteristics (such as the enhanced vegetation index or the net primary productivity) have been shown to yield advantages over the NDVI in terms of stress detection in plants, the NDVI is still in frequent use. Despite its lower sensitivity to changes of the vegetation cover, the NDVI is a conservative, robust measurement tool (Pettorelli, 2013) and has been comprehensively studied regarding its relationship with temperature variability (see, e.g., Halpert, 1993, 1995;Kawabata et al, 2001;Karnieli et al, 2010;Kim et al, 2010). The global data availability for a relatively long period of observations has made NDVI easily applicable to remote sensing studies without the need for exhaustive preprocessing.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, research on climatic drivers of NDVI variations has often concentrated on a global scale (e.g., the aforementioned Halpert, 1993, 1995;Kawabata et al, 2001;Karnieli et al, 2010;Kim et al, 2010), whereas regional studies like Wang et al (2003) and Hao et al (2012) are still rare. In the face of global warming, however, especially inter-regional climate disparities are projected to increase (Ciscar et al, 2011;Iglesias et al, 2012), thus emphasizing the need for regional research.…”
Section: Introductionmentioning
confidence: 99%
“…In the whole study area, the nine atmospheric circulation factors influenced coupling features of spring NPP and precipitation more greatly in the areas southern to latitude 30N°. Gong et al (2002) and Kawabata et al (2001) have also proved that spring vegetation activity in the northern hemisphere is sensitive to climate changes.…”
Section: Regress Analysis Of Npp With Atmospheric Circulation Factorsmentioning
confidence: 90%